2008
DOI: 10.1088/0957-4484/19/7/075103
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of highly stabilized nanocrystalline silver particles by a non-pathogenic and agriculturally important fungusT. asperellum

Abstract: A controlled and up-scalable biosynthetic route to nanocrystalline silver particles with well-defined morphology using cell-free aqueous filtrate of a non-pathogenic and commercially viable biocontrol agent Trichoderma asperellum is being reported for the first time. A transparent solution of the cell-free filtrate of Trichoderma asperellum containing 1 mM AgNO(3) turns progressively dark brown within 5 d of incubation at 25 °C. The kinetics of the reaction was studied using UV-vis spectroscopy. An intense sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
250
1
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 479 publications
(268 citation statements)
references
References 28 publications
14
250
1
3
Order By: Relevance
“…3). The broad intense band close to 3402/cm may be assigned to the N-H stretching frequency arising from peptide linkages (Mukherjee et al 2008). The presence of peak at 3416/cm could be ascribed to O-H group in polyphenols or proteins/ enzymes or polysaccharides (Susanto et al 2009).…”
Section: Resultsmentioning
confidence: 97%
“…3). The broad intense band close to 3402/cm may be assigned to the N-H stretching frequency arising from peptide linkages (Mukherjee et al 2008). The presence of peak at 3416/cm could be ascribed to O-H group in polyphenols or proteins/ enzymes or polysaccharides (Susanto et al 2009).…”
Section: Resultsmentioning
confidence: 97%
“…The assimilation of different nanoparticles such as SiO 2 , clay, TiO 2 , KMnO 4 , nano cellulose, nano fibrillated cellulose and carbon nanotubes are capable of amending the packaging material in terms of mechanical and barrier properties (Tsai et al, 2010;Reddy et. al., 2007;Xie et al, 2012;Hejri et al, 2013;Saeidnia et al, 2013;Mukherjee et al, 2014;Yang and Yao, 2014). It has been reported that packaging material mechanical properties such as ductile strength, shear strength, barrier potential, thermal constancy and optical characteristics of polymers can be enhanced by assimilating nano materials into their matrices (Zhong et al, 2007).…”
Section: Nano Compositementioning
confidence: 99%
“…Edible coating is done with the help of liquid film forming solution onto the surface of the food products. They are created by casting or by traditional plastic extrusion techniques (Park et al, 1996).…”
Section: Edible Nano Coatings and Nano Coating Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…So the interests of researchers have turned towards green synthesis. The metal-microbe interactions have an important role in several biotechnological applications, and microorganisms are considered as potential biofactory for the synthesis of nanoparticles [22][23][24][25][26][27]. Gold nanoparticles are considered biocompatible but chemical synthesis methods may still lead to the presence of some toxic chemical species absorbed on the surface that may have adverse effects in medical applications [28].…”
Section: Introductionmentioning
confidence: 99%